Overcoming cloning problems by staining agarose gels with crystal violet instead of ethidium bromide in lactate dehydrogenase gene from Plasmodium vivax and Plasmodium falciparum - Turgut-Balik, D; Çelik, V; Moreton, K; Brady, RL (Akademiai Kiado Zrt, 2005)
In this study, lactate dehydrogenase gene from Plasmodhan vivax has been tried to subclone into an expression vector. Some of the Plasmodium falciparum lactate dehydrogenase mutant genes have also been tried to clone and subclone into a vector, but we failed to clone or subclone either of the genes. DNA visualisation in electrophoretic gels typically requires UV radiation and the fluorecent dye ethidium bromide. A crystal violet-stained gel was run instead of an ethidium bromide gel and so avoided the use of UV radiation. This enabled us to clone or subclone both Plasmodium vivax lactate dehydrogenase gene and Plasmodium falciparum lactate dehydrogenase mutant genes into any desired vector.
Keywords: Plasmodium vivax; Plasmodium falciparum; lactate dehydrogenase; crystal violet; ethidium bromide